2014
DOI: 10.1111/jzo.12122
|View full text |Cite
|
Sign up to set email alerts
|

Altitudinal variation in maternal investment and trade‐offs between egg size and clutch size in the Andrew's toad

Abstract: Environmental variation along altitudinal gradients can promote life‐history trait differentiation in ectothermic animals. Life‐history theory predicts that increased environmental stress results in a shift in reproductive allocation from offspring quantity to quality and a stronger trade‐off between egg size and clutch size. To test this prediction, we investigated patterns of variation in life‐history traits (i.e. age, body size, clutch size and egg size) among four populations of Bufo andrewsi from Baoxing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 58 publications
0
28
0
Order By: Relevance
“…Again, similar to other taxonomic groups, anurans and urodeles from high-altitudes invest in larger eggs but reduce offspring number (Liao et al 2014) and increase mean and maximum age, as well as maturation age (Zhang and Lu 2012). Apart from intrinsic trade-offs, hypoxia has been evoked as a possible cause of increased longevity in high-altitude regions (Zhang and Lu 2012).…”
Section: Amphibiansmentioning
confidence: 76%
“…Again, similar to other taxonomic groups, anurans and urodeles from high-altitudes invest in larger eggs but reduce offspring number (Liao et al 2014) and increase mean and maximum age, as well as maturation age (Zhang and Lu 2012). Apart from intrinsic trade-offs, hypoxia has been evoked as a possible cause of increased longevity in high-altitude regions (Zhang and Lu 2012).…”
Section: Amphibiansmentioning
confidence: 76%
“…In external fertilizers, greater egg number has been predicted to select for larger gonads in males due to higher sperm demand (Emerson 1997), whereas larger eggs are thought to weaken that selection pressure as sperm will be more likely to collide with them (Levitan 1993). In fact, altitudinal variation in egg volume and/or clutch size is widespread in frogs, although the direction of their covariation can differ between species (Lüddecke 2002;Chen et al 2013;Liao et al 2014). A comparison of insular populations of F. limnocharis revealed that large females lay larger but fewer eggs (Xu et al 2013).…”
Section: Testis Massmentioning
confidence: 96%
“…Towards high altitudes, where the activity period is shorter, B. andrewsi attain a larger size at metamorphism, a higher longevity, and a larger body size at slower growth rates (Liao and Lu 2012;Liao et al 2015). At low altitude, on the other hand, males have more time for food acquisition and reproduction, and food is also more abundant (Liao andLu 2009, 2012;Liao et al 2014). As common for anurans, B. andrewsi is characterized by indeterminate growth.…”
Section: Introductionmentioning
confidence: 95%